Cyclophilin A predicts clinical outcome in patients with congestive heart failure undergoing endomyocardial biopsy. (February 2013) - Zuern, Christine S.; Müller, Karin A.L.; Seizer, Peter; Geisler, Tobias; Banya, Winston; Klingel, Karin; Kandolf, Reinhard; Bauer, Axel; Gawaz, Meinrad; May, Andreas E.
<x xml:space="preserve">Abstract</x> Aims Cyclophilin A (CyPA) represents a ubiquitous intracellular protein, which is secreted by inflammatory and by dying/necrotic cells. The aim of this study was to evaluate the prognostic relevance of CyPA expression in endomyocardial biopsies of consecutive patients with congestive heart failure. Methods and results A total of 227 unselected patients (age 53.9 ± 15 years) with congestive heart failure undergoing endomyocardial biopsy for diagnostic reasons were enrolled. Biopsies were analysed using established histopathological and immunohistological criteria together with CyPA staining. Virus genome was studied by polymerase chain reaction. CyPA was significantly enhanced in patients with inflammatory cardiomyopathy (n = 127) as compared with patients with non‐inflammatory cardiomyopathy (n = 100, P < 0.0001). During a mean follow‐up of 16.3 months, 60 patients (26.4%) reached the primary endpoint, a composite of all‐cause death, heart transplantation, malignant arrhythmia, and heart failure‐related rehospitalization. Of all clinical (ejection fraction, New York Heart Association functional class), laboratory (brain natriuretic peptide), and immunohistological parameters (CyPA, extracellular matrix metalloproteinase inducer, CD68, CD3, major hisocompatibility complex II, and virus genome) tested, only CyPA was identified as an independent predictor for the composite endpoint [hazard ratio (HR) 2.4; 95% confidence interval (CI) 1.2–5.2; P = 0.019] as well as for all‐cause death and heart transplantation alone (HR 4.7; 95% CI 1.1–19.8; P = 0.036). Subgroup analysis revealed CyPA as a predictor in patients with non‐inflammatory cardiomyopathy for the composite endpoint (HR 3.0; 95% CI 1.3–6.6; P = 0.007) as well as all‐cause death or heart transplantation alone (HR 6.4; 95% CI 1.4–28.1; P = 0.014). Conclusions CyPA is an independent predictor of clinical outcome in patients with congestive heart failure undergoing endomyocardial biopsy.